(untitled) (The Research of Medical Science Review, 2025)
The poultry industry is undergoing a significant transition towards antibiotic-free production in response to growing public health concerns about antimicrobial resistance and residual contamination in animal products. Modulating gut microbiota via nutritional interventions, such as probiotics, has emerged as a promising way to sustain broiler health and performance without the need for antibiotics. This study aimed to assess and compare the effects of probiotic and antibiotic supplementation on gut microbiota diversity, immunological response, intestinal morphology, and overall productivity in broiler chickens. A controlled feeding trial was conducted at University of Veterinary and Animal Sciences, Lahore, Punjab, Pakistan, over six weeks, involving 90 Ross 308 broiler chicks that were randomly allocated into three groups: control (no supplementation), antibiotic-treated (oxytetracycline), and probiotic-treated (Lactobacillus acidophilus). The measured key metrics included body weight gain, feed conversion ratio (FCR), mortality rate, immunological markers (IL-6 and IgA), Shannon diversity index of gut microbiota, and duodenal villus height. Statistical analysis was performed using one-way ANOVA, accompanied by Tukey’s post-hoc test to ascertain group differences. Broilers treated with probiotics demonstrated a markedly greater increase in body weight and an improved feed conversion ratio compared to the control and antibiotic groups. Moreover, IL-6 concentrations decreased, and IgA levels increased in the probiotic group, indicating an enhanced immunological response. The probiotic group exhibited the highest variety of gut flora, and histological investigation revealed considerably elongated intestinal villi, indicating improved nutrient absorption. The data indicates that probiotics can successfully substitute antibiotics in broiler diets, enhancing growth performance, immunological modulation, and gut health of broilers. This study offers a viable, antibiotic-free option for chicken breeders, supporting ongoing efforts to mitigate antimicrobial resistance in animal agriculture.